HUBUNGAN POWER OTOT LENGAN DENGAN KEMAMPUAN JODAN TSUKI PADA ATLET SHORINJI KEMPO DOJO POASIA - Ayu Asriwaty; Asmuddin; Badaruddin (Universitas Halu Oleo, 2021)
The Correlation between Arm Muscle Power on Jodan Tsuki Ability at The Shorinji Kempo Athletes Dojo Poasia. The first advisor by Mr. Dr. Asmuddin, S.Pd., M.Pd and the second advisor by Mr. Badaruddin, S.Pd., M.Pd. Department of Health and Recreation Physical Education, Faculty of Teacher Training and Education, Halu Oleo University, Kendari. The purpose of this study was to determine the correlation between arm muscle power on jodan tsuki ability at the shorinji kempo thletes Dojo Poasia. The population in this study the total number of shorinji kempo athletes at Dojo Poasia 35 consistat 30 male athletes and 5 female athletes by using purposive sampling technique. The instrument used to measure of tests arm muscle power by using a test medicine ball put, while the instrument used to measure the jodan tsuki ability by using test jodan tsuki for 30 seconds by 3 times the chance. The research data were analyzed by using the statistical technique product moment. The results obtained from testing the hypothesis show that rxy = 0.55 ˃ r table at a significant level of 0.05 = 0.361. The coefficient determination of arm muscle power on jodan tsuki ability of 0.30 or 30%. This shows that the level of correlation between the variable arm muscle power (X) and the ability of jodan tsuki (Y) is 30%. Its mean that 70% is influenced by other biomotor elements, such as: strength, accuracy, speed, flexibility, coordination, balance, and reaction. It can be concluded that there is a significant correlation between arm muscle power on jodan tsuki ability at the shorinji kempo thletes Dojo Poasia